The Construal of Attitudinal Resources in the Discourse of the Song Titled “Returning Happiness to the People” By Gen. Prayuth Chan-ocha: An Appraisal Analysis - Badklang, Cheewala; Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The objective of the paper is to identify and analyze the attitudinal resources of the song titled “Returning Happiness to the People” by the leader of National Council for Peace and Order (NCPO) who wrote the lyric while the military coup has happened since 2014. The main theoretical framework I draw upon in this paper is Appraisal theory (Martin, 1997, 2000; Martin & Rose, 2003; Martin & White, 2005) that developed from Systemic Functional Linguistics (Halliday, 1994; Halliday & Matthiessen, 2004). The important of this paper is to unfold the discourse analysis of a sample of the popular song from Thai military who want to convey the message to Thai people. This work can contribute to a better understanding of how this song Gen.Prayuth Chan-ocha negotiates interpersonal meanings with Thai people.